2018
DOI: 10.1007/s00234-018-1997-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cerebral perfusion in perimesencephalic subarachnoid hemorrhage and aneurysmal subarachnoid hemorrhage

Abstract: PMH patients had better cerebral perfusion compared to patients with aSAH, particularly during the vasospasm time window. After stratifying for the amount of blood, PMH patients also had better cerebral perfusion in the first 72 h after SAH. These results are in line with the better clinical presentation and prognosis of PMH, and possibly with a different etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Severely increased intracranial pressure is rare at the onset of PNSAH due to the low incidence of low-pressure venous hemorrhage, which indicates that patients with PNSAH have good cerebral perfusion ( 42 ). Fragata et al's ( 43 ) study of CT perfusion showed that patients with PNSAH had better cerebral perfusion than aneurysmal SAH patients in the first 72 h.…”
Section: Definition and Variantmentioning
confidence: 99%
“…Severely increased intracranial pressure is rare at the onset of PNSAH due to the low incidence of low-pressure venous hemorrhage, which indicates that patients with PNSAH have good cerebral perfusion ( 42 ). Fragata et al's ( 43 ) study of CT perfusion showed that patients with PNSAH had better cerebral perfusion than aneurysmal SAH patients in the first 72 h.…”
Section: Definition and Variantmentioning
confidence: 99%